Three-dimensional kinematic differences between accurate and high velocity kicks in rugby union place kicking - Sinclair, J.; Taylor, P. J.; Smith, A.; Bullen, J.; Bentley, I.; Hobbs, S. J. (International Journal of Sports Science & Coaching, 2017)
Place kicking occurs many times during a rugby union game with more than half of all points scored coming from place kicking. Ball velocity is an important biomechanical indicator of kicking success, but it also evident that the ball must be kicked accurately to pass between the posts. This study aimed to identify biomechanical differences in rugby place kicking kinematics when kicking towards a specific target and for maximum velocity. Ten male rugby union kickers performed place kicks in two conditions: (1) for maximum velocity and (2) towards a pre-defined target. Lower extremity kinematics were obtained using an optoelectric motion capture system operating at 500 Hz. Differences in lower extremity kinematics between the two kicking conditions were examined using paired t-tests. Higher ball velocities were obtained when kicking for maximum velocity. Foot linear velocity, knee extension velocity and hip extension velocity were also found to be greater when kicking for maximum velocity. Ankle dorsiflexion and peak external rotation were found to be greater in the accuracy condition. The findings suggest that rugby kickers may have selected distinct kicking mechanics characterised by reduced joint angular velocities and a more externally rotated foot position in a deliberate attempt to improve precision, sacrificing ball velocity and thus the distance that the ball can be kicked. The specific findings from the current work have implications for coaches and applied practitioners which may facilitate improvements in kicking performance. ABSTRACT FROM AUTHOR